ChemInform Abstract: Straightforward Synthesis of 2‐Propylquinolines under Multicomponent Conditions in Fluorinated Alcohols. Issue 46 (24th October 2013) - Venkateswarlu, Ch.; Balaji, P. V.; De, Kavita; Crousse, Benoit; Figadere, Bruno; Legros, Julien
Abstract A 3‐component Povarov reaction between butyraldehyde, aromatic amines and ethyl vinyl ether in trifluoroethanol followed by an oxidation, offers a convenient entry to differently substituted 2‐propylquinolines.